ดีเอ็นเอจากซองกระสุน กระสุน และปลอกกระสุน ด้วยวิธีไดเร็คพีซีอาร์ - ภูวดล ธนะเกียรติไกร (มหาวิทยาลัยสงขลานครินทร์, 2023)
Cartridges, bullets, and casings (CBCs) are commonly encountered in shooting incidences and could provide valuable DNA information from touch DNA that has been left during bullet handling and gun loading; however, conventional DNA analysis has yielded very poor results. Direct PCR, in which the DNA extraction and quantification steps are bypassed, has been shown to provide comparable and sometimes improved results from touch DNA and trace DNA samples. Here, we aimed to apply direct PCR with bullet casings (from three ammunition types and guns) and evaluate whether it should be recommended as a standard operating protocol for forensic DNA analysts. Three experiments were carried out to investigate the following: the effect of firing on DNA deposited on bullet cosings; the effect of gun and ammunition types on STR profile quality; and the feasibility of using direct PCR with actual cases via typing of mock casework samples. DNA extraction resulted in a loss of about 40% of DNA originally deposited, and firing a bullet decreased the amount of DNA recovered by 27%6. We recovered means (and 95% credible intervals) of 11.1 (7.9 to 13.9), 5.6 (3.0 to 7.7), 2.3 (0.2 to 4.0) alleles from touch DNA on fired bullet casings using the direct PCR protocol, conventional extraction protocol, and dilution protocol, respectively. No statistical difference in alleles recovered was observed between different fired ammunition types from three guns (9mm, 7.62 mm, and 5.56 mm from Glock Model 19, AK47, and Tavor T-21, respectively). As expected, mixed 'DNA profiles were observed in 40% of mock casework samples in which guns are shared between volunteers, which can complicate profile interpretation. This study showed that direct PCR from bullet casings improved STR profiles. As the direct PCR protocol is quicker, cheaper, and resulted in more alleles recovered, forensic DNA analysts may benefit from using direct PCR.